Microbiological quality of whole and filleted shelf-tilapia - Gatti Junior, Pedro [UNESP]; Assuncao, Argos W. A. [UNESP]; Baldin, Juliana C. [UNESP]; Amaral, Luiz A. [UNESP] (Elsevier B.V., 2014)
Despite fish being a rich source of animal nutrients and having numerous associated health benefits, it is an extremely perishable food, prone to a wide range of hazards. The bacterial load associated with shelf-whole-fish organs (e.g. digestive tracts and skin) or mishandling of fish may be a vehicle of infection and become a risk to public health. The objective of this paper is to evaluate the microbiological quality of whole ungutted and filleted shelf-tilapia, as well as assess the safety for human consumption. For this purpose, in order to investigate the distribution and occurrence of bacterial populations, the count of total and thermotolerant coliforms, coagulase-positive Staphylococcus and presence of Salmonella spp. was determined. This paper shows that all fish organs were contaminated with thermotolerant coliform. Skin and fillet show higher populations and occurrence of all microorganisms analyzed. Lower bacterial populations were recovered from the gut and muscles of whole tilapia. Two samples of fillet were contaminated with coagulase-positive Staphylococcus. It can be concluded that the skin and filleted tilapia are important carriers of food-borne pathogens. In addition, fish might become an important cross and self-contamination source. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Fish; Fillet; Tilapia; Self-contamination; Coagulase-positive Staphylococcus; Thermotolerant coliforms